Physics Learning Innovation: Song and Animation-Based Media as a Learning Solution for Mirrors and Lenses for Junior High School Students - Zakiyah, Zakiyah; Boonma , Kantida; Collado, Resty (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to develop and assess the effectiveness of a physics learning media based on songs and animations to enhance motivation and understanding among Grade VIII students on the topics of mirrors and lenses.. Methodology: The study employed a mixed-methods approach, utilizing a procedural development model by Borg and Gall. Tools and software used include Adobe Audition 1.5, Wondershare Filmora, and Adobe Flash CS6. Data collection methods included questionnaires and expert reviews. Main Findings: The song and animation-based learning media received a "Very Valid" rating from content experts (90%) and a "Valid" rating from media experts (70%), with teachers giving an average score of 90%. The t-test results showed a significant increase in students' motivation in the experimental group, with a mean score of 79.50 compared to 68.07 in the control group, indicating the positive impact of the developed media. Novelty/Originality of this study: This study introduces an innovative approach by combining musical and animated elements in physics education, thereby stimulating both the left and right brain hemispheres. This dual-hemisphere engagement fosters a more interactive and enjoyable learning experience, bridging the gap in traditional physics instruction by addressing both logical and creative aspects of student learning.